2003
DOI: 10.1007/s00406-003-0419-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral networks linked to the event-related potential P300

Abstract: P300 is an event-related potential that is elicited by an oddball paradigm. In several neuropsychiatric diseases, differences in latencies and amplitude compared to healthy subjects have been reported. Because of its clinical significance, several investigations have tried to elucidate the intracranial origins of the P300 component. In the present study we could demonstrate a network of P300 generators. Investigated were 15 healthy subjects with an acoustical oddball paradigm within a fMRI block design, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 37 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…For one, many of these studies did not have adequate coverage of the hippocampus (Casey et al, 2001;Kirino et al, 2000;McCarthy et al, 1997;Menon et al, 1997). Neuroimaging studies, which have scanned the whole brain, may also have failed to detect hippocampal activation (Ardekani et al, 2002;Downar et al, 2002;Higashima et al, 1996;Horn et al, 2003;Linden et al, 1999;Opitz et al, 1999) due to susceptibility artifacts in this region (Veltman et al, 2000). These artifacts result from abrupt changes in magnetic susceptibility that occurs across tissue interfaces such as the border between air-filled sinuses and brain parenchyma or between bone and brain parenchyma.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For one, many of these studies did not have adequate coverage of the hippocampus (Casey et al, 2001;Kirino et al, 2000;McCarthy et al, 1997;Menon et al, 1997). Neuroimaging studies, which have scanned the whole brain, may also have failed to detect hippocampal activation (Ardekani et al, 2002;Downar et al, 2002;Higashima et al, 1996;Horn et al, 2003;Linden et al, 1999;Opitz et al, 1999) due to susceptibility artifacts in this region (Veltman et al, 2000). These artifacts result from abrupt changes in magnetic susceptibility that occurs across tissue interfaces such as the border between air-filled sinuses and brain parenchyma or between bone and brain parenchyma.…”
Section: Discussionmentioning
confidence: 92%
“…A number of neuroimaging studies have examined brain responses to the oddball task; these studies have provided evidence for the involvement of largescale distributed network involving mainly the dorsolateral prefrontal cortex, anterior cingulate cortex, and the posterior parietal cortex (Ardekani et al, 2002;Casey et al, 2001;Downar et al, 2002;Higashima et al, 1996;Horn et al, 2003;Kiehl et al, 2001;Kirino et al, 2000;Linden et al, 1999;McCarthy et al, 1997;Menon et al, 1997;Opitz et al, 1999;Stevens et al, 2000;Yoshiura et al, 1999). Only two of these studies have reported responses in medial temporal lobe regions.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, P3 latency is considered a measure of stimulus evaluation speed and has been associated with mental processing speed (for review, see Linden 2005;Polich 2007). Research has linked a broad network of brain regions to the P3 generation (Horn et al 2003;Linden 2005) and there is evidence that P3 components reflect indirect modulating effects from dopamine, acetylcholine, noradrenaline, or serotonin neuromodulators (Hansenne 2000;Polich and Criado 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This view is supported by the observed activation in right IFG (BA 44), left IFG (BA 45), and ACC also only by motion standstill. Taken together, by motion standstill we observed activation of a typical attention network [see Corbetta and Shulman, 2002 Furthermore, this network is also activated by visual [Kirino et al, 2000;Linden et al, 1999] and acoustic [Horn et al, 2003] target detection paradigms. Therefore, the r-IPL posterior can be regarded as a multimodal area, an area activated together with the anterior attentional network by orienting reaction towards unresolved or target stimuli.…”
Section: Activation Of the Posterior Part Of The Right Ipl (R-ipl Posmentioning
confidence: 83%